Preface - Kratochvíl, Lukáš (Philos Trans R Soc Lond B Biol Sci, 2021)
This preface introduces the two parts of a theme issue on vertebrate sex chromosome evolution (title below). We invited and edited 22 articles concerning the following main topics (Part 1): sex determination without sex chromosomes and/or governed by epigenetics; origin of sex-determining genes; reasons for differentiation of sex chromosomes and differences in their rates of differentiation as well as (Part 2): co-option of the same linkage groups into sex chromosomes; is differentiation of sex chromosomes a unidirectional pathway?; consequences of differentiated sex chromosomes; differences in differentiation of sex chromosomes under male versus female heterogamety; evolution of sex chromosomes under hybridization and polyploidy. This article is part of the theme issue ‘Challenging the paradigm in sex chromosome evolution: empirical and theoretical insights with a focus on vertebrates (Part I)’.